2020
DOI: 10.3389/fgene.2020.00464
|View full text |Cite
|
Sign up to set email alerts
|

Gene Panel Analysis in a Large Cohort of Patients With Autosomal Dominant Polycystic Kidney Disease Allows the Identification of 80 Potentially Causative Novel Variants and the Characterization of a Complex Genetic Architecture in a Subset of Families

Abstract: Among 158 distinct variants, 80 (50.6%) were previously unreported, confirming broad allelic heterogeneity. Eleven patients showed more than one variant. Segregation analysis indicated biallelic disease in five patients, digenic in one, de novo variant with unknown phase in two. Furthermore, our NGS protocol allowed the identification of two patients with somatic mosaicism, which was undetectable with Sanger sequencing. Among patients without PKD1/PKD2 variants, we identified three with possible alternative di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
38
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(43 citation statements)
references
References 53 publications
3
38
0
Order By: Relevance
“…In total, this variant has now been reported in 6 cases of PKD-VEO making it the most common recurrent PKD1 hypomorphic variant associated with this phenotype 4 5 9 . We also detected the variants, PKD1 variant has been reported in another family with 2 VEO cases 24 . Although previously reported as a 'likely' pathogenic variant 4 , it is frequent in population studies, has been found with a truncating pathogenic variant in several pedigrees (phase not established) and listed on the PKD mutation database as 'indeterminate', consistent with a hypomorphic role.…”
Section: Recurrent Pkd1 Hypomorphic Variantssupporting
confidence: 58%
See 1 more Smart Citation
“…In total, this variant has now been reported in 6 cases of PKD-VEO making it the most common recurrent PKD1 hypomorphic variant associated with this phenotype 4 5 9 . We also detected the variants, PKD1 variant has been reported in another family with 2 VEO cases 24 . Although previously reported as a 'likely' pathogenic variant 4 , it is frequent in population studies, has been found with a truncating pathogenic variant in several pedigrees (phase not established) and listed on the PKD mutation database as 'indeterminate', consistent with a hypomorphic role.…”
Section: Recurrent Pkd1 Hypomorphic Variantssupporting
confidence: 58%
“…p.(Thr2873Ile) is present on 57 alleles in GnomAD but was inherited in cis with the p.(Arg2191His) variant, detected in 37 alleles in GnomAD (case 13): the number of alleles with both variants present is not presently available in GnomAD but it is possible that the combination of both in cis is more deleterious. The c.9499A>T p.(Ile3167Phe) variant has been reported both as an 'indeterminate' variant and observed in trans in another family with 2 cases of PKD-VEO 24 . However it has been detected on 340 alleles in gnomAD including 2 homozygotes (highest MAF 0.002).…”
Section: Terminology Acmg Classification and Reportingmentioning
confidence: 95%
“… 8 , 28 , 29 Ninety percent of patients with ADPKD have an identified variant, 85% of which are within the large and difficult to sequence PKD1 gene while 15% are in PKD2 , with most of the identified mutations being private within a specific family. 6 , 30 - 35 ADPKD shows genetic heterogeneity as variants in multiple other genes have been shown to produce a similar phenotype including GANAB , DNAJB11 , HNF1B , VHL , UMOD , MUC1 , and others. 29 , 33 , 35 - 38 Patients and providers find the results of genetic testing in ADPKD beneficial in prognostication, family and transplant planning, and treatment, and advocate for access to testing.…”
Section: Introductionmentioning
confidence: 99%
“… 6 , 30 - 35 ADPKD shows genetic heterogeneity as variants in multiple other genes have been shown to produce a similar phenotype including GANAB , DNAJB11 , HNF1B , VHL , UMOD , MUC1 , and others. 29 , 33 , 35 - 38 Patients and providers find the results of genetic testing in ADPKD beneficial in prognostication, family and transplant planning, and treatment, and advocate for access to testing. 25 , 29 , 39 - 41 …”
Section: Introductionmentioning
confidence: 99%
“…While exemptions from dominant and recessive inheritance in ADPKD and ARPKD have been reported before (Mantovani et al, 2020;Obeidova et al, 2020), we aim at illustrating the complexity of PKD genetics through peculiar genetic alterations of both PKD1 and PKHD1 in three young adult females and one male infant. The presented examples demonstrate unusual modes of inheritance and exceptional clinical presentations, challenging the given disease ontology in PKD.…”
Section: Introductionmentioning
confidence: 99%